Analysis Of The Impact Of Telecommunications Infrastructure And Goods Expenditure On Gross Domestic Product ( Period 2000-2023) - Jhon Daniel Kasih Sihotang; Hutapia Hutapia (Journal of Research in Social Science and Humanities, 2024)
This research aims to analyze the influence of telecommunications infrastructure and government spending on goods on gross domestic product (GDP) in Indonesia in the period 2000-2023. The analysis method used is linear regression. The dependent variable for this research is the Gross Domestic Product (GDP); the independent variables are the number of broadband network users, cell phone users, and goods expenditure. The results of the research show that cell phone use and shopping for goods have a positive and significant effect on gross domestic product in Indonesia, while the broadband network user variable does not have a significant effect on gross domestic product. This research provides new insight into the importance of digital economic integration and telecommunications infrastructure development as supporting factors for gross domestic product (GDP) development.